Design and fabrication of mechanical sand purifier / Ahmad Aiman Suhaimi - Suhaimi, Ahmad Aiman (2023)
First, my objective towards this project is to make the job for workers easier. I designed a sand purifier that will filter all the unneeded substances in the sand and will pack it into a sandbag. The problem with the traditional sand filter or purifier is that it takes two work to filter and pack the sand. So, with my project will help workers to do their job faster. My second objective towards this project is to reduce the cost of the sand purifier. In recent years, most sand purifiers are quite expensive, especially automated machines. I want to make a simple sand purifier by using mechanical parts and of course it is more affordable. It runs using an electric motor that will shake the filter. Just simply put the sand on it and it will filter it. This machine is also equipped with funnel as a way for the sand to fall directly into the sandbag or ground